L’identité Cain-ri ou comment se créer une identité culturelle à l’heure de la mondialisation ? - David Sudre (Études Caribéennes)
By means of its control over mediascapes, especially represented both by television and Internet, American basketball and its culture has gradually grown in the landscape of hexagonal basketball, becoming today the major reference for a large number of French players. Certain young players from Parisian suburbs, who rightly made theirs the nickname of "Cain-ris", strongly appropriate to themselves the standards and values of this sports and cultural movement from the US, modifying this way their cultural practices and their identity. The objective of the article is then to analyze the complexity of this “Cain-ri” identity, an identity created within the specific context of globalization, taking roots on both sides of the Atlantic Ocean